The impact of dysphagia prehabilitation on swallowing outcomes post‐chemoradiation therapy in head and neck cancer: A systematic review. (28th December 2021) - Brady, Rhona; McSharry, Laura; Lawson, Susan; Regan, Julie
Abstract: Introduction: This study aimed to summarise research findings on dysphagia prehabilitation initiated before chemoradiation therapy (C)RT in head and neck cancer (HNC) including its impact on three swallow‐related outcomes at distinct time points. Methods: A comprehensive search was completed in PubMed, Embase, Web of Science and CINAHL. Inclusion criteria were studies of adults with HNC with an exercise‐based prehabilitation programme beginning before (C)RT. Methodological quality was rated using the Downs and Black checklist. The Template for Intervention Descriptions and Replication (TIDieR) checklist was used to evaluate how well studies were reported. Results: Eight studies (three randomised control trials) involving 295 adults with HNC were included. The largest participant group (63%) were Stage III/IV head and neck squamous cell carcinoma (HNSCC). Prehabilitation was completed independently at home (100%) and typically began 2 weeks before CRT (75%). Studies evaluated the impact of dysphagia prehabilitation across functional ( n  = 6), quality of life ( n  = 5) and physiological ( n  = 4) domains. Prehabilitation significantly altered physiological (25%), functional (66%) and quality of life (50%) outcomes. Fifty per cent of studies included long‐term (>1 year) outcomes. Quality of included studies ranged from poor (25%) to good (38%). Six (75%) studies reported sufficient details of exercise programmes. Conclusion: Limited evidence supports exercise‐based dysphagia prehabilitation before (C)RT to improve swallow‐related outcomes, and long‐term benefits remain unclear. Further high‐quality research using core outcome sets is required.